Removing Short Wavelengths From Polychromatic White Light Attenuates Circadian Phase Resetting in Rats - Gladanac, Bojana; Jonkman, James; Shapiro, Colin M.; Brown, Theodore J.; Ralph, Martin R.; Casper, Robert F.; Rahman, Shadab A. (Frontiers in Neuroscience, 2019)
Visible light is the principal stimulus for resetting the mammalian central circadian pacemaker. Circadian phase resetting is most sensitive to short-wavelength (blue) visible light. We examined the effects of removing short-wavelengths <500 nm from polychromatic white light using optical filters on circadian phase resetting in rats. Under high irradiance conditions, both long- (7 hours) and short- (1 hour) duration short-wavelength filtered (<500 nm) light exposure attenuated phase-delay shifts in locomotor activity rhythms by (~40-50%) as compared to unfiltered light exposure. However, there was no attenuation in phase resetting under low irradiance conditions. Additionally, the reduction in phase-delay shifts corresponded to regionally specific attenuation in molecular markers of pacemaker activation in response to light exposure, including c-FOS, Per1 and Per2. These results demonstrate that removing short-wavelengths from polychromatic white light can attenuate circadian phase resetting in an irradiance dependent manner. These results have important implications for designing and optimizing lighting interventions to enhance circadian adaptation.